The biographical-narrative method. A tool for educational research - Ma. del Rosario Landín Miranda; Sandra Ivonne Sánchez Trejo (Pontificia Universidad Católica del Perú, 2019)
One of the methods that has allowed us to explore in a different way our knowledge about teaching practice and education in general has been the biographical-narrative. We consider that the biographical-narrative method leads us to capture that genuine knowledge that a subject constructs from his experience lived in different spaces and times, allowing us to understand the true essence of education. In this work we integrate part our research experience with this method, addressing its contributions in the field of education, the obstacles to its development and its recognition as a different way of generating knowledge.